Preparation Of A Stabilized Nano-Lignin Emulsifier From Oil Palm Empty Fruit Bunch - Sekeri, Siti Hajar (2022)
A study was carried out to determine the effectiveness of lignin, extracted from oil palm (Elaeis guineensis) biomass as a water-in-oil (W/O) emulsifier. To achieve this goal, soda lignin (SL) was extracted via soda pulping process and a series of nanosized soda lignin (NSL) was prepared using a homogenizer at three different speeds i.e., 10400 rpm (NSL 10), 11400 rpm (NSL 11), and 12400 rpm (NSL 12) for one hour.